Implementación de un motor – generador de corriente continua, en el laboratorio de máquinas eléctricas de la Universidad Técnica de Cotopaxi para realizar prácticas demostrativas - Moreta Guayaquil, Verónica Pilar (2015)
This research is about the implementation process of an engine-generator with continuous current functional and practical. It is suitable for small-scale demonstration operation practices at different load variations. A practical demonstration module in order to analyze the performance and behavior of the machine was developed. The variables were voltage, current, speed for different load variations. They could be visualized by the application of instruments implemented in the control panel and possible solutions, as well as the practical aspects. This practical module has an operating manual and guidelines that enable the equipment correct use….